2012
DOI: 10.3791/3813
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Differentiation of Mouse Embryonic Stem Cells into Motor Neurons

Abstract: Direct differentiation of embryonic stem (ES) cells into functional motor neurons represents a promising resource to study disease mechanisms, to screen new drug compounds, and to develop new therapies for motor neuron diseases such as spinal muscular atrophy (SMA) and amyotrophic lateral sclerosis (ALS). Many current protocols use a combination of retinoic acid (RA) and sonic hedgehog (Shh) to differentiate mouse embryonic stem (mES) cells into motor neurons [1][2][3][4] . However, the differentiation efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 11 publications
(8 reference statements)
2
26
0
2
Order By: Relevance
“…In order to differentiate Wharton's jelly stem cell into motor neuron-like cells in this study, RA was utilized along with Shh similar to those carried out by Liqing et al [44]. The combination of RA and Shh are commonly used for inducing the expression of transcription factors which play important roles in motor neuronal differentiation [45,46]. Differentiated neurons in different groups were then characterized morphologically and for the expression of motor neuron markers including Nestin, PAX6, NF-H, Islet-1, HB9, and Chat in mRNA levels and protein by quantitative reverse transcription PCR and immunocytochemistry, respectively.…”
Section: Evaluation Of Wjmscs Differentiation Into Motor Neuron-like mentioning
confidence: 98%
“…In order to differentiate Wharton's jelly stem cell into motor neuron-like cells in this study, RA was utilized along with Shh similar to those carried out by Liqing et al [44]. The combination of RA and Shh are commonly used for inducing the expression of transcription factors which play important roles in motor neuronal differentiation [45,46]. Differentiated neurons in different groups were then characterized morphologically and for the expression of motor neuron markers including Nestin, PAX6, NF-H, Islet-1, HB9, and Chat in mRNA levels and protein by quantitative reverse transcription PCR and immunocytochemistry, respectively.…”
Section: Evaluation Of Wjmscs Differentiation Into Motor Neuron-like mentioning
confidence: 98%
“…heat stress) (Dormann and Haass, 2013;Dormann et al, 2012;Dormann et al, 2010). Of note, all these data were derived from non-neuronal models and/or by heterologous expression of the mutant FUS variants (Wu et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Wu et al reported a two-step differentiation protocol that improved the motor neuron differentiation efficiency to 51 %. In that study, the first step was “neutralization” by adding Noggin and fibroblast growth factors (FGFs) to the cell culture medium [3]. The second step was to induce motor neuron specification.…”
Section: Introductionmentioning
confidence: 99%